Triagem de microrganismos isolados no estado da Bahia para biotransformação de compostos esteroidais - Moreira, Josineide Silva (2009)
The pharmaceutical industry is now introducing biotechnological processes in large scale and thus replacing multiple stages of chemical syntheses. Microorganisms are efficient biocatalysts of many processes as the conversion of steroidal compounds, which have great importance for the synthesis of pharmaceuticals. Steroids are organic substances with medical importance that have a cyclopentanophenanthrene nucleus, and are used in anti-inflammatory therapy and contraception, among others. This study aimed to select microorganisms in the state of Bahia capable of catalyzing conversions of steroids compounds. For this screening we used two substrates, a mixture of phytosterols containing β-sitosterol, stigmasterol and campesterol and a steroid, the 19-nor-4-androstene-3,17-dione. As biocatalysts it were used cultures of Saccharomyces cerevisiae from sugar cane brandy distilleries of Bahia state, rhizobacteria isolated in south of Bahia and endophytic fungi. The products were analyzed by gas chromatography coupled to mass spectrometry to verify the degradation of substrates. In the case of phytosterols, from 10 yeasts, 10 bacteria and 7 fungi evaluated, only the endophyte fungi CDC86 was able to degrade a mixture of campesterol, stigmasterol and β-sitosterol. In the screening using the steroid 19-nor-4-androstene-3, 17-dione, the 22 microorganisms evaluated (5 yeasts, 10 bacteria and 7 fungi), 19 were able to act as biocatalysts, with the exception of reactions with the bacteria I68 and fungi MDF77 and CDC86. Several products were observed with rates of bioconversion up to 76% depending on the microorganism used and the reaction time. Two steroids, nandrolone and estrone, were identified. The results indicated the biocatalytic potential of microorganisms isolated in the state of Bahia, so further investigation should be performed to optimize the process.